The roles of triiodothyronine and irisin in improving the lipid profile and directing the browning of human adipose subcutaneous cells - de Oliveira, Miriane [UNESP]; Mathias, Lucas Solla [UNESP]; Rodrigues, Bruna Moretto [UNESP]; Mariani, Bianca Gonçalves [UNESP]; Graceli, Jones Bernardes; De Sibio, Maria Teresa [UNESP]; Castro Olimpio, Regiane Marques [UNESP]; Fontes Moretto, Fernanda Cristina [UNESP]; Deprá, Igor Carvalho [UNESP]; Nogueira, Célia Regina [UNESP] (Elsevier, 2020)
Triiodothyronine (T3) and irisin (I) can modulate metabolic status, increase heat production, and promote differentiation of white adipose tissue (WAT) into brown adipose tissue (BAT). Herein, human subcutaneous white adipocytes were treated with 10 nM T3 or 20 nM I for 24 h to evaluate intracellular lipid accumulation, triglyceride, and glycerol levels, oxidative stress, DNA damage, and protein levels of uncoupling protein 1 (UCP1), adiponectin, leptin, peroxisome proliferator-activated receptor gamma (PPARγ), and fibronectin type III domain-containing protein 5 (FNDC5). T3 and irisin improved UCP1 production, lipid profile, oxidative stress, and DNA damage. T3 elevated adiponectin and leptin levels with a concomitant decrease in PPARy and FNDC5 levels. However, irisin did not alter adipokine, PPARy, and FNDC5 levels. The results indicate that T3 may be used to increase leptin and adiponectin levels to improve insulin sensitivity, and irisin may be used to prevent obesity or maintain weight due to its impact on the lipid profile without altering adipokine levels.
Keywords: Fat; Lipid accumulation; Oxidative stress; RNA-Seq; Thyroid hormone